Trust transfer effects and associated risks in telemedicine adoption - Leonie Kuen; Fiona Schürmann; Daniel Westmattelmann; Sophie Hartwig; Shay Tzafrir; Gerhard Schewe (Electronic Markets, 2023)
Telemedicine has the potential to address considerable challenges in the efficient provision of health care services. However, this will not be realized until a high acceptance rate among patients is achieved. We address the research gap that arises from the need to explore the interplay of different trust referents (physician, technology, treatment) and perceived risk dimensions (performance, privacy, time, psychological) in patients' telemedicine adoption considering two different symptom types (physical vs. mental). We conducted a scenario-based online survey and performed t -tests, scenario-specific structural equation modeling, and multi-group analysis. T -tests and multi-group analysis do not indicate differences in perceptions and path coefficients between the symptoms. Furthermore, scenario-specific structural equation modeling reveals that for both scenarios, trust in physician is less important for trust transfer effects and intention to use than trust in technology and trust in treatment. Trust in treatment has similar effects for all risk dimensions, while only performance risk relates to use intention. Moreover, the results indicate a considerable intention-behavior gap. We advance IS research by emphasizing the relevance of considering multiple trust referents, trust transfer effects, and a multidimensional perspective on perceived risk.
Keywords: I12; D91; 620; Trust transfer; Multidimensional risk; Telemedicine; Technology adoption; Patient